Физика прочности волокнистых композиционных материалов с металлической матрицей - Шоршоров М. Х. Минас Хачатурович; Устинов Л. М. Лев Михайлович; Гукасян Л. Е. Леонид Егишович; Виноградов Л. В. Леонид Викторович (Москва, Металлургия, 1989)
Авт. указаны на обороте тит. л.